High-risk behaviors and their association with awareness of HIV status among participants of a large-scale prevention intervention in Athens, Greece - Pavlopoulou, Ioanna D. (BMC Public Health, 2020)
BACKGROUND: Aristotle was a seek-test-treat intervention during an outbreak of human immunodeficiency virus (HIV) infection among people who inject drugs (PWID) in Athens, Greece that started in 2011. The aims of this analysis were: (1) to study changes of drug injection-related and sexual behaviors over the course of Aristotle; and (2) to compare the likelihood of risky behaviors among PWID who were aware and unaware of their HIV status. METHODS: Aristotle (2012–2013) involved five successive respondent-driven sampling rounds of approximately 1400 PWID each; eligible PWID could participate in multiple rounds. Participants were interviewed using a questionnaire, were tested for HIV, and were classified as HIV-positive aware of their status (AHS), HIV-positive unaware of their status (UHS), and HIV-negative. Piecewise linear generalized estimating equation models were used to regress repeatedly measured binary outcomes (high-risk behaviors) against covariates. RESULTS: Aristotle recruited 3320 PWID (84.5% males, median age 34.2 years). Overall, 7110 interviews and blood samples were collected. The proportion of HIV-positive first-time participants who were aware of their HIV infection increased from 21.8% in round A to 36.4% in the last round. The odds of dividing drugs at least half of the time in the past 12 months with a syringe someone else had already used fell from round A to B by 90% [Odds Ratio (OR) (95% Confidence Interval-CI): 0.10 (0.04, 0.23)] among AHS and by 63% among UHS [OR (95% CI): 0.37 (0.19, 0.72)]. This drop was significantly larger (p = 0.02) among AHS. There were also decreases in frequency of injection and in receptive syringe sharing in the past 12 months but they were not significantly different between AHS (66 and 47%, respectively) and UHS (63 and 33%, respectively). Condom use increased only among male AHS from round B to the last round [OR (95% CI): 1.24 (1.01, 1.52)]. CONCLUSIONS: The prevalence of risky behaviors related to drug injection decreased in the context of Aristotle. Knowledge of HIV infection was associated with safer drug injection-related behaviors among PWID. This highlights the need for comprehensive interventions that scale-up HIV testing and help PWID become aware of their HIV status.